Do conferences drive quality improvement in accounting research? - Muhammad Nur Abdullah Birton; Maryati Maryati; Muhammad Muttaqin (Journal of Accounting and Investment, 2023)
Research aims: In Indonesia, the Simposium Nasional Akuntansi (SNA) and regional accounting conferences (RAC) exist. Prior studies on their database are constrained and predominantly adopt an external viewpoint. Therefore, using an "insider" perspective, this study aims to reveal how scientific conferences impact knowledge quality and dissemination in accounting research.Design/Methodology/Approach: This study took the case of the Konferensi Ilmiah Akuntansi (KIA) X Jakarta at Universitas Muhammadiyah Jakarta. Data were analyzed descriptively sourced from the KIA X committee and the selection process of 235 manuscripts until acceptance/rejection by the journal.Research findings: The results demonstrated that, first, KIA X engaged 58 institutions and 235 manuscripts as participants, with 70 reviewers representing cohosting institutions and journal editorial teams across Indonesia. Second, reviewers independently deemed 160 manuscripts suitable for journal publication and 75 for proceedings. Among these, 130 were accepted by SINTA 2-5 journals, and 30 await confirmation. Third, accounting conferences seem to satisfy formalities rather than significantly enhancing knowledge or practice quality.Theoretical contribution/Originality: Regional conferences like KIA X aim to foster discussions on accounting concepts, knowledge, and innovations. Nevertheless, if proceedings reflect poor quality, the intended scientific objectives falter. Hence, this study delves into this concern through conference database analysis.Practitioner/Policy implication: The RAC committees face challenges in balancing convenience, appeal, and competitiveness, all while dispelling the notion of lower manuscript quality compared to SNA.